2019
DOI: 10.1002/cpt.1529
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged‐Release Tacrolimus Is Less Susceptible to Interaction With the Strong CYP3A Inhibitor Voriconazole in Healthy Volunteers

Abstract: The nature and extent of drug-drug interactions between oral drugs is affected by numerous modulators. The effect of the formulation (prolonged release (PR) vs. immediate release (IR)) of a victim drug during treatment with a CYP3A (cytochrome P450 enzyme 3A4) inhibitor is unknown but expected to be smaller with PR. We studied PR and IR tacrolimus during treatment with the strong CYP3A inhibitor voriconazole in 18 healthy volunteers in a pharmacokinetic, four-phase, crossover trial. The exposure increase was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…Inclusion and exclusion criteria were very similar to those used in our previous trial. 7 In the present trial, female volunteers could be included if they were using highly effective contraceptive measures. Female-specific exclusion criteria were pregnancy, lactation, and Fridericia's corrected QT interval >460 milliseconds.…”
Section: Trial Design and Participantsmentioning
confidence: 99%
“…Inclusion and exclusion criteria were very similar to those used in our previous trial. 7 In the present trial, female volunteers could be included if they were using highly effective contraceptive measures. Female-specific exclusion criteria were pregnancy, lactation, and Fridericia's corrected QT interval >460 milliseconds.…”
Section: Trial Design and Participantsmentioning
confidence: 99%
“…Second, we did not take into account the dosage form of oral tacrolimus during the treatment with voriconazole. Andrew et al has found out that pro-longed tacrolimus is less susceptible to interaction with voriconazole in healthy volunteers [14] . Third, our prediction results require further validation from more real-world data to implement the findings.…”
Section: Discussionmentioning
confidence: 99%
“…After the rat-based PBPK model was built up successfully, it was scaled to whole-body PBPK model of human. And the datasets from three clinical trails [14,30] were used to evaluate the performance of human PBPK model. The model performance was evaluated using two methods.…”
Section: Pbpk Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Differences in the extent of metabolism by CYP3A enzymes also make LCPT less susceptible to certain drug interactions. 11 Additionally, a lower Cmax achieved by LCPT decreases peak-related side effects, such as neurotoxicities. 12 Both the regulated absorption and reduction in peaks have led to speculation that use may reduce opportunistic infections, such as BK polyomavirus, but this theory requires further investigation.…”
Section: Extended-release Tacrolimus Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%